1999
DOI: 10.1016/s0893-133x(98)00114-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of the MscI Polymorphism of the Dopamine D3 Receptor Gene with Tardive Dyskinesia in Schizophrenia

Abstract: In 112 schizophrenic patients previously treated with typical neuroleptics, we investigated the putative role of the dopamine D3 receptor gene (DRD3) in tardive dyskinesia (TD). Patients were assessed for TD severity using the Abnormal Involuntary Movement Scale (AIMS) and were subsequently genotyped for the MscI polymorphism that identifies a serine to glycine substitution in DRD3. A modified analysis of covariance model, which incorporated several clinical risk factors for TD, was utilized to detect differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 68 publications
8
78
1
5
Order By: Relevance
“…The severity of TD has also been observed to increase with age in conformity with other reports. 4,11,22 However, severity of TD was higher among males compared to females in our study, which is in contrast to other reports. 23,24 This may be due to sampling variation or may reflect a variation unique to Indian population.…”
Section: Discussioncontrasting
confidence: 99%
“…The severity of TD has also been observed to increase with age in conformity with other reports. 4,11,22 However, severity of TD was higher among males compared to females in our study, which is in contrast to other reports. 23,24 This may be due to sampling variation or may reflect a variation unique to Indian population.…”
Section: Discussioncontrasting
confidence: 99%
“…This was not true of DRD3 which, intriguingly, was found to be associated with TD by our group 4 and by Basile et al 5 and is a widely although not universally replicated genetic association with TD. [9][10][11] On the other hand, there was a significant age effect of HTR2A for which there was a disparity between our findings 2 and those of Basile et al 3 As noted, the sample examined by Basile et al 3 was two decades younger, on average, than our sample.…”
Section: Agementioning
confidence: 48%
“…This disparity contrasts with similar findings of the two groups in the same patient samples in regard to association of the dopamine D3 receptor gene (DRD3) with TD. 4,5 Among the demographic and clinical factors that have been associated with individual susceptibility to TD, age is the most consistently reported. In a prospective study, Jeste et al 6 found the cumulative incidence of TD in patients who initiated treatment with antipsychotic drugs after the age of 45, to be 60% after 3 years.…”
Section: Agementioning
confidence: 99%
“…In order to shed light on these controversial results, recently, Lerer et al 6 performed a combined analysis including data from 780 patients from six research centers, dividing patients into eight groups based on their population origin. Most of the data have been published previously either in peer reviewed journals [43][44][45][46][47] or in abstract form 48,49 (see Table 2 for more details). The authors applied stepwise logistic regression, and confounding effects of group, age and gender were taken into account.…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…The two genetic variants DRD3 Ser9Gly (Steen et al 43 ) and CYP1A2 C734A (presented in our additive, co-recessive model of interaction as mentioned above) were published (Basile et al 33,44 ) without Genetics of tardive dyskinesia DJ Müller et al protecting the potential intellectual property. In our academic culture, it is commonplace to publicize our findings rapidly to promote replication and wide use of the information.…”
Section: Outlook: Clinical Implicationsmentioning
confidence: 99%